Benzyl N '-(1-methyl-1H-indol-2-ylmethylene)hydrazinecarbodithioate - Khaledi, H.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2008)
In the title compound, C(18)H(17)N(3)S(2), the dihedral angle between the planes of the aromatic ring systems is 83.63 (16)degrees. In the crystal structure, inversion dimers occur, linked by pairs of N-H center dot center dot center dot S hydrogen bonds.